Collaging Cultures: Curating Italian Studies. (2nd January 2019) - Duncan, Derek
Abstract : This essay aims to contribute to current debates about how to research and teach within the disciplinary frame of modern languages in light of the knowledge that recent patterns of global migration have made the conventional fusion of national territory and language untenable. The challenge is to reimagine histories of cultural practice and production critically in spite of the national frame that continues to shape our thinking. Starting from theoretical prompts by Doris Sommer and Okwui Enwezor, I suggest that contemporary curatorial practice offers one model for reworking how we practice Italian Studies in light of the decolonizing imperatives of work in diasporic, postcolonial, and transnational studies. Emphasizing a spatial model of cultural connectedness, I work with a notion of the haptic to investigate (as a kind of case study) how an encounter with the variegated traces of Italian culture in Scotland may lead researchers and students toward a pragmatic understanding of connectivity that does not depend on the blood lines of what Sommer calls "inherited frameworks." I argue that contemporary curatorial practices revising both the optics and ownership of (Italian) culture can radically alter the presuppositions of our research and pedagogy.